1980
DOI: 10.1136/bmj.280.6229.1397
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of childhood asthma to adult life.

Abstract: Summary and conclusionsA randomly selected group of 331 children who had started to wheeze in childhood and a control group of 77 children were prospectively studied clinically and physiologically from 7 to 21 years of age. Most subjects improved during adolescence and about 55% of those whose wheezing had started before 7 years and stopped before adolescence remained wheeze free. Forty-five per cent of subjects who had apparently ceased to wheeze at 14 years had minor recurrences of wheezing between 14 and 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
124
5
4

Year Published

1984
1984
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 279 publications
(142 citation statements)
references
References 15 publications
9
124
5
4
Order By: Relevance
“…Seven of these studies did not find a are asymptomatic subjects who have bronchial difference in outcome (1,28,47,50,(58)(59)(60), another responsiveness, but do not perceive induced bronone found women to have a better prognosis than chial obstruction during histamine provocation men (41), and two found female sex to be associ- (64). The same is true of asthmatic subjects, some ated with a poor outcome (32,55). reporting little discomfort with severe airway In the Melbourne study, which started in 1964, obstruction, whereas others experience marked 401 children were randomly selected from 30 000 (55) could not support this hypothesis.…”
Section: Sexmentioning
confidence: 78%
See 4 more Smart Citations
“…Seven of these studies did not find a are asymptomatic subjects who have bronchial difference in outcome (1,28,47,50,(58)(59)(60), another responsiveness, but do not perceive induced bronone found women to have a better prognosis than chial obstruction during histamine provocation men (41), and two found female sex to be associ- (64). The same is true of asthmatic subjects, some ated with a poor outcome (32,55). reporting little discomfort with severe airway In the Melbourne study, which started in 1964, obstruction, whereas others experience marked 401 children were randomly selected from 30 000 (55) could not support this hypothesis.…”
Section: Sexmentioning
confidence: 78%
“…Most patients with asthma have clinical and serologic evidence of atopy. The results of studies examining the relationship of allergy to the outcome of asthma from childhood to adulthood are conflicting: some investigators found no effect on the outcome (32,(75)(76)(77), whereas others did (39,41,48,56,78,79). The studies which have shown an effect all point to a negative association of atopy with the outcome of asthma.…”
Section: Atopymentioning
confidence: 81%
See 3 more Smart Citations